Photomagnetic molecular and extended network Langmuir–Blodgett films based on cyanide bridged molybdenum–copper complexes1. Issue 22 (11th March 2015) - Bridonneau, Nathalie; Long, Jérôme; Cantin, Jean-Louis; von Bardeleben, Jurgen; Talham, Daniel R.; Marvaud, Valérie
<x xml:space="preserve">Abstract</x> The present manuscript describes two types of cyanide bridged molybdenum–copper photomagnetic films obtained by the Langmuir–Blodgett technique.